Perancangan Sistem Informasi Penjualan Gudang Sirine Berbasis Web Dengan Menggunakan Metode Prototype - Surya Adji Pangestu; Muhammad Feizal (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Gudang Sirine is a company engaged in the field of warning equipment, such as sirens, strobes, and other accessories for official vehicles, which was established about seven years ago. Gudang Sirine aims to meet the needs related to warning equipment for police vehicles and other institutions. With the rapid development of information systems, the ordering process at Gudang Sirine is still conducted manually, making it less efficient and effective. Currently, sales information systems have become critical for the operational management of various organizations and companies. In this thesis, the author designs and implements an information system that enanles efficiemt order management, there by facilitating the admin in managing orders.